Let's find the difference between each number.
38-14=24
74-38=36
122-74=48
182-122=60
254-182=72
As you can tell, you're adding 12 to each difference before. The next difference would be 72+12=84. Let's add.
254+84=338
Now the next difference would be 84+12=96.
338+96=434
So, the next two terms are 338 and 434.
Answer:
angle YUT = 120
Step-by-step explanation:
in Triangle SUT
angle 70 + angle 50 + angle x = 180
70 + 50 + x = 180
120 + x = 180
x = 180 - 120
x = 60
angle SUT = 60
angle SUT + angle YUT = 180 ( straight line)
60 + x = 180
x = 120
Therefore angle YUT ( exterior angle ) = 120
Answer:
x = 1/4
y = -1/2
z = 9/4
Step-by-step explanation:
Here we have a system of 3 equations with 3 variables:
4*x + 2*y + 1 = 1
2*x - y = 1
x + 3*y + z = 1
The first step to solve this, is to isolate one of the variables in one of the equations, let's isolate "y" in the second equation:
2*x - y = 1
2*x - 1 = y
Now that we have an expression equivalent to "y", we can replace this in the other two equations:
4*x + 2*(2*x - 1) + 1 = 1
x + 3*(2*x - 1) + z = 1
Now let's simplify these two equations:
8*x - 1 = 1
7*x - 3 + z = 1
Now, in the first equation we have only the variable x, so we can solve that equation to find the value of x:
8*x - 1 = 1
8*x = 1 + 1 = 2
x = 2/8 = 1/4
Now that we know the value of x, we can replace this in the other equation to find the value of z.
7*(1/4) -3 + z = 1
7/4 - 3 + z = 1
z = 1 + 3 - 7/4
z = 4 - 7/4
z = 16/4 - 7/4 = 9/4
z = 9/4
Now we can use the equation y = 2*x - 1 and the value of x to find the value of y:
y = 2*(1/4) - 1
y = 2/4 - 1
y = 1/2 - 1
y = -1/2
Then the solution is:
x = 1/4
y = -1/2
z = 9/4
Step-by-step explanation:
f=6×9
aubstituting f=6×9
6×9×16=b
864=b